Birth Satisfaction During the Early Months of the COVID-19 Pandemic in the United States. Issue 1 (January 2022) - Mollard, Elizabeth; Kupzyk, Kevin
Abstract: Purpose: The purpose of this study was to describe birth satisfaction in women who gave birth in U.S. hospitals during the earliest months of the COVID-19 pandemic (March–July 2020). Study Design and Methods: A cross-sectional survey of 747 postpartum women who gave birth in the United States during the early COVID-19 pandemic was conducted. Participants in the United were recruited via social media. They completed a questionnaire that included demographic, health, and obstetric experience questions, and the Birth Satisfaction Scale-Revised. Descriptive statistics, t -tests, analysis of variance (ANOVA) models, and nonparametric correlations were performed. Results: Higher birth satisfaction scores were associated with higher income, marriage, white race, vaginal birth, having a birth partner present, and sufficient support during birth. Factors negatively associated with birth satisfaction were separation from infant, unplanned cesarean birth, neonatal intensive care unit admission, hypertension, preeclampsia, hemorrhage, depression, and anxiety. Clinical Implications: Presence of birth partners, sufficient birth support, and minimizing separation of mother and infant improve birth satisfaction. Obstetric complications, including unplanned cesarean birth, negatively affect birth satisfaction. There are racial disparities in birth satisfaction. It is critical to develop further interventions to end racism in maternal health care. Abstract : During the early months of the COVID-19 pandemic, there were many restrictive changes to childbirth practices in the inpatient setting geared toward reducing viral spread and keeping patients and health care workers safe. In this study 747 women who gave birth in the United States during the first several months of the pandemic offer their perspectives on how these changes affected their childbirth experience and overall satisfaction.